The effects of Instagram users' gratification on psychological response, and continued usage intention from the perspective of uses and gratification and Stimulus-Organism-Response theory - Jin, Dian; Wan Abas, Wan Anita; Kamarudin, Syafila (Human Resource Management Academic Research Society, 2023)
Scholars have started to research the effect of satisfaction on users' willingness to continue using social media, such as Facebook, Instagram, Weibo. However, few studies have focused on the effects of these gratification on users’ psychological responses, such as satisfaction and emotional attachment. To bridge this knowledge gap, this study, based on uses and gratification and Stimulus-Organism-Response theory, integrated a new model to study the influence of gratification on psychological response, and the influence of psychological response on Instagram continuance use intention. A sample of students (N = 209) from Universiti Putra Malaysia was selected for this study. PLS-SEM was mainly used for hypothesis testing during data analysis. The results indicate that entertaining value, social value, social participation, and utilitarian value positively affect users' satisfaction. Emotional attachment is significantly influenced by social participation, information consumption. Moreover, psychological response positively affects continued usage intention. In addition, this study can help social media practitioners better understand users' intention to continue using from the perspective of their gratifications and psychological response.